COMMUNITY-BASED OBESITY EDUCATION USING AUDIOVISUAL MEDIA TO ENHANCE KNOWLEDGE - Enis, Rina Nofri; Shafira, Nyimas Natasha Ayu; Herlambang, Herlambang; Syauqy, Ahmad; Fitri, Amelia Dwi; Puspasari, Anggelia; Maharani, Citra; Kusdiyah, Erny; Aurora, Wahyu Indah Dewi; Delfira, Annissa; Sulistiawan, Andika; Arisya, Qothrunnada (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2026)
Background: Obesity is a growing public health concern associated with an increased risk of non-communicable diseases. Improving public knowledge through health education is an important strategy for promoting healthy lifestyles and preventing obesity. Audiovisual media have been widely adopted to enhance educational effectiveness and participant engagement. Objective: This study evaluated the effectiveness of a community-based obesity education program using PowerPoint presentations and an educational video to improve participants' knowledge. Methods: A pre-experimental one-group pretest–posttest design was conducted among community participants in Jambi, Indonesia, in 2026. Participants completed a 10-item multiple-choice questionnaire before and after the educational session. The intervention covered the definition of obesity, body mass index classification, waist circumference, risk factors, complications, and lifestyle-based prevention strategies. Data were analyzed using the Shapiro–Wilk test and the Wilcoxon signed-rank test, with statistical significance set at p < 0.05. Results: Forty-five participants completed both assessments. The mean knowledge score increased from 86.67 ± 12.25 at baseline to 94.89 ± 6.95 after the intervention. The distribution of score differences was non-normal (Shapiro–Wilk: W = 0.749, p < 0.001). The Wilcoxon signed-rank test demonstrated a significant improvement in knowledge following the educational intervention (W = 0, p < 0.001). Participant evaluation also indicated high acceptance of the educational program across all assessed domains, including material quality, video presentation quality, perceived educational benefits, and overall participant satisfaction. Conclusion: The community-based obesity education program effectively improved participants' knowledge and was well accepted by the participants. Integrating presentations with audiovisual media represents a practical approach to strengthening health literacy and supporting community-based obesity prevention. Keywords: audiovisual education; obesity; community intervention; health promotion; knowledge.